FENOMENA SOSIAL PERCERAIAN DAN DAMPAK AGROSOSIOEKONOMI PERCERAIAN PEGAWAI NEGERI SIPIL DI KECAMATAN MALALAYANG KOTA MANADO - Jessi Mariska Pangkey; Maria Henny Pratiknjo; Femmy ., Tasik (AGRI-SOSIOEKONOMI, 2021)
This study aims to determine the social phenomenon of civil servant divorce in Malalayang SubDistrict, Manado City. The research method used in this study is a qualitative descriptive approach which was carried out in Malalayang Sub-District with 6 informants using interview techniques to be able to uncover, describe and understand the phenomena that occur. Methods of data collection used areÂ  the method of observation, interviews and documentation. The data analysis technique used is descriptive qualitative analysis. The results of this study indicate that in general the root cause of economic factors is the husband's ability in the household which causes disputes and disputes that never stop. Divorce is more dominant than the wife because of economic factors and disputes. Another factor is the presence of a third party (infidelity), and the lack of maturity, as an institution that is not yet optimal. The phenomenon of divorce can be changed if there is a systematic effort through education and community and religious institutions and religious leaders cooperate directly, and awareness of the importance of maintaining love in domestic life, because the real prototype lies in the person himself.